Caudal block vs. transversus abdominis plane block for pediatric surgery: a systematic review and meta-analysis - Hafeman, Michael; Greenspan, Seth; Rakhamimova, Emiliya; Jin, Zhaosheng; Moore, Robert P.; Al Bizri, Ehab (Frontiers in Pediatrics, 2023)
Background: The caudal block and transversus abdominis plane block (TAP) are commonly used in combination with general anesthesia for pediatric lower abdominal, inguinal, and genitourinary surgeries. There is limited data directly comparing the impact of these techniques on recovery. In this meta-analysis, we compare the duration of postoperative analgesia between these two techniques. Objective: This review examined the duration of analgesia in pediatric patients (age 0-18yrs) undergoing surgery who received caudal or TAP block after induction of general anesthesia. The primary outcome was duration of analgesia, defined as the time to first rescue analgesic dose. Secondary outcomes included number of rescue analgesic doses, acetaminophen usage within 24 hours postoperatively, 24hr pain score area under the curve, and postoperative nausea and vomiting. Evidence Review: We systematically searched Pubmed, Central, EMBASE, CINAHL, Google Scholar, Web of Science citation index, the US clinical trials register, and abstracts from prominent 2020-2022 anesthesia conferences for randomized controlled trials that compared these blocks and reported analgesia duration. Findings: Twelve RCTs inclusive of 825 patients were identified. TAP block was associated with longer analgesia duration (Mean difference = 1.76 hours, 95% CI 0.70 to 2.81, p = 0.001) and reduced doses of rescue analgesic within 24 hours (Mean difference 0.50 doses, 95% CI 0.02 to 0.98, p = 0.04). No statistically significant differences were detected in other outcomes. Conclusion: This meta-analysis suggests that TAP block provides greater duration of analgesia than caudal block after pediatric surgeries. TAP block was also associated with fewer rescue analgesic doses in the first 24 hours without increased pain scores.